A ESTATÍSTICA NOS ANOS INICIAIS DO ENSINO FUNDAMENTAL - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
Statistics are applied in various fields of knowledge and in many contexts and their teaching is present in all stages of basic education. Here is a brief history on the development and teaching of statistics and a history of the city of Porto União and state schools in the city. Through a qualitative and quantitative approach to research we drew a profile of teachers of primary education Years Initials of the municipality as well as the difficulties encountered by teachers in teaching Statistics in Early Years. The analysis of the Statistics Teaching in municipal public schools is based on the National Curriculum Standards and Curriculum Proposal of Mathematics of the state of Santa Catarina. They are proposed activities to Statistics teaching in Years Elementary School Initials that may impact on teaching practice in the classroom. At the end of this dissertation is a discussion of the application of some of the activities suggested to understand the possibilities and the difficulties encountered by teachers in the implementation of activities in the classroom during the approach to the subject.
A ESTATÍSTICA NOS ANOS INICIAIS DO ENSINO FUNDAMENTAL
Keywords: Estatística; Ensino de estatística; Anos Iniciais do Ensino Fundamental; atividades; Statistics; Statistics teaching; Years Elementary School Initials; Activities; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA